2022
DOI: 10.1098/rspb.2022.1840
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-species bird flocks re-assemble interspecific associations across an elevational gradient

Abstract: Understanding how non-trophic social systems respond to environmental gradients is still a challenge in animal ecology, particularly in comparing changes in species composition to changes in interspecific interactions. Here, we combined long-term monitoring of mixed-species bird flocks, data on participating species' evolutionary history and traits, to test how elevation affected community assemblages and interspecific interactions in flock social networks. Elevation primarily affected flocks through reassembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 79 publications
(138 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, similar findings of elevational changes in flock characteristics (species richness, compositional turnover and flock organization) have been made in other montane systems (e.g. [ 87 90 ]), suggesting montane flocks in other regions of the world might also be more dynamic and open than their lowland counterparts. Further studies should focus on testing the generality of the open-membership hypothesis in other mountain ranges.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, similar findings of elevational changes in flock characteristics (species richness, compositional turnover and flock organization) have been made in other montane systems (e.g. [ 87 90 ]), suggesting montane flocks in other regions of the world might also be more dynamic and open than their lowland counterparts. Further studies should focus on testing the generality of the open-membership hypothesis in other mountain ranges.…”
Section: Discussionsupporting
confidence: 72%
“…In particular, one limitation of our analysis is that we did not distinguish potential partner species from one another, instead lumping them into a single category (heterospecifics). Other recent studies of mixed-species groups have found that dyadic patterns of social associations among species may be reshaped by environmental variation [68,91], suggesting that this may be a fruitful avenue for further research.…”
Section: Discussionmentioning
confidence: 99%
“…These two species associate closely in MSFs from Nepal to northeastern India, Myanmar, southwest China and even southeastern China (e.g. Shen et al [42]). Once thought to be close relatives, they are now thought to be in different genera [43].…”
Section: Plumage Similarities In Mixed-species Flocksmentioning
confidence: 99%